Late transcatheter recanalization of a closed ductus arteriosus in a 2-month-old infant with tetralogy of Fallot and isolated left pulmonary artery - Aziez Ahmed; Gary Anthony LaCroix; Anas Hasan Bader Ishqair; Pushpa Shivaram; Srikant Das (Wolters Kluwer Medknow Publications, 2020)
Ductal stenting is increasing as an alternative to surgical shunts in cyanotic newborns. However, most reports include newborns with patent ducts who are often on prostaglandin before the procedure. We report a successful late transcatheter recanalization of the closed ductus arteriosus in a 2-month-old infant with tetralogy of Fallot, right aortic arch, and an isolated left pulmonary artery (LPA). We achieved adequate LPA growth before complete repair. There were no procedural complications. This procedure is rare in Western countries due to universal pulse oximetry screening and increased fetal diagnoses. The procedure is technically challenging in the absence of any angiographic flow into the ductus. Evidence of a ductal ampulla increases the chances of success.